The Difficulty Of Physics Education Students Class 2018 In Studying Quantum Physics Courses Online - Almianai, Rini; Soewarno, Soewarno; Farhan, Ahmad; Musdar, Musdar (Asian Journal of Science Education, 2022)
Problem-solving in the Quantum Physics course which requires a very mathematical description and analysis is considered difficult by students, especially if the learning is done online. This study aims to find out the difficulties of learning Quantum Physics courses through online learning for physics education students in class 2018 FKIP USK. The subjects in this study were students of physics education class 2018 who took the Quantum Physics course, totaling 49 people. The research approach used is descriptive quantitative. Data collection was carried out using a closed questionnaire based on the google form. The results showed that students had learning difficulties using online learning in the Quantum Physics course from internal factors, namely cognitive indicators with a total score of 841 while external factors, namely community environmental indicators, with a total score of 457. Conclusions Based on the difficulties experienced by students in this study, it can be seen that students have some difficulties in studying Quantum Physics material online.